Emergence of Skilled Behaviors in Professional, Amateur and Junior Cricket Batsmen During a Representative Training Scenario - Connor, Jonathan D.; Farrow, Damian; Renshaw, Ian (Frontiers in Psychology, 2018)
The aim of this study was to explore the emergence of skilled behaviours, in the form of actions, cognitions and emotions, between professional state level cricket batters and their lesser skilled counterparts. Twenty-two male cricket batsmen (n = 6 state level; n = 8 amateur grade club level, n = 8 junior state representative level) participated in a game scenario training session against right arm pace bowlers (n = 6 amateur senior club). The batsmen were tasked with scoring as many runs as possible during a simulated limited-overs game. The actions, cognitions and emotions of each batsmen were recorded in situ with findings showing differences between state level players and those lesser skilled. State level batsmen played more scoring shots and scored more runs, underpinned by superior bat-ball contact and technical efficiency. Furthermore, the state player’s cognitive evaluations of their own performance differed from junior batters, with more reported strategies based on an external outcome focus, such as where to score runs, rather than a focus on internal processes, such as making technical changes. State level batsmen also reported lower levels of nervousness compared with junior level batsmen. These results highlight the importance of viewing the emergence of skilled behaviour as multi-faceted, rather than simply the acquisition of superior execution and technical proficiency.